Introduction and implementation of the CMRP radiodosimeter — a novel wireless microdosimetry system. (1st March 2022) - Vohradsky, J.; Chartier, L.; Pogossov, A.; Alnaghy, S.; Paino, J.; Peracchi, S.; Pan, V.; Povoli, M.; Kok, A.; Tran, L.T.; Rosenfeld, A.B.
Abstract: Microdosimetry is a useful method to evaluate the relative biological effectiveness (RBE) as well as dose equivalent of any mixed radiation field without prior knowledge of type of charged particles and their spectra. The need of portable, user friendly devices for microdosimetric Quality Assurance measurements in particle therapy are greatly preferable to avoid sophisticated setup and time-consuming data analysis. Currently, the ability to perform microdosimetric measurements is restricted to those with extensive prior knowledge of the electronics involved and their experimental setup. The Centre for Medical Radiation Physics (CMRP) has developed a compact microdosimetric system named Radiodosimeter - a novel acquisition system that combines both wireless communication and plug-and-play design to provide a device that can be used with minimal setup. The system is compatible with current CMRP MicroPlus probe technology. The Radiodosimeter communicates with the client computer via Wi-Fi, allowing remote management and monitoring of acquisitions. The system was bench-marked against the standard microdosimetric setup at Heavy Ion Medical Accelerator in Chiba (HIMAC), Japan and was found to have the same response. Several redundancy methods were demonstrated such as continuing an acquisition following disconnection from the client software and the ability to connect through different Wi-Fi modes (WPA2 Personal/Enterprise). These features prove that the Radiodosimeter can operate independently of a client computer, indicating its potential to be used as a portable device for personal monitoring in mixed radiation fields, including for microdosimetric quantity verification predicted by Treatment Planning Software in particle therapy.